Silicone-Induced Granuloma after Injection for Cosmetic Purposes: A Rare Entity of Calcitriol-Mediated Hypercalcemia. (9th December 2013) - Agrawal, Nidhi; Altiner, Sinan; Mezitis, Nicholas H. E.; Helbig, Sina
Abstract : Hypercalcemia is often a clue to the presence of unsuspected illness. We present an interesting case of an HIV-positive transgender female with a rare cause of silicone-induced granulomatous hypercalcemia. Although there have been a few case reports of silicone injections in dialysis patients causing hypercalcemia, this metabolic derangement secondary to silicone granulomas continues to be a unique entity with an unclear pathophysiology. We present a 45-year-old transgender HIV-positive female, with extensive silicone injections, who presented with symptomatic hypercalcemia. Workup for malignancy and hyperparathyroidism was negative. 1, 25-Dihydroxyvitamin D level and 24-hour urine calcium level were elevated. CT scan showed extensive high-density reticulonodular densities in the buttocks and gluteal muscle fascia extending upwards to the lumbar region, along with prominent external iliac and inguinal lymph nodes. Nuclear imaging showed diffuse heterogeneity and increased uptake in the buttocks, most consistent with granuloma calcifications, and an inguinal lymph node biopsy confirmed a foreign body giant cell reaction. The patient was started on prednisone and this resulted in decrease in serum and urinary calcium levels. Physicians should have a high index of suspicion for silicone-induced hypercalcemia considering the growing prevalence of body contour enhancement with injections, implants, and fillers using this material.